Functions of TRPs in retinal tissue in physiological and pathological conditions - Nascimento, Thaianne Hanah Oliveira do; Pereira-Figueiredo, Danniel; Veroneze, Louise; Nascimento, Amanda Alves; De Logu, Francesco; Nassini, Romina; Campello-Costa, Paula; Faria-Melibeu, Adriana da Cunha; Souza Monteiro de Araújo, Daniel; Calaza, Karin Costa (Frontiers in Molecular Neuroscience, 2024)
The Transient Receptor Potential (TRP) constitutes a family of channels subdivided into seven subfamilies: Ankyrin (TRPA), Canonical (TRPC), Melastatin (TRPM), Mucolipin (TRPML), no-mechano-potential C (TRPN), Polycystic (TRPP), and Vanilloid (TRPV). Although they are structurally similar to one another, the peculiarities of each subfamily are key to the response to stimuli and the signaling pathway that each one triggers. TRPs are non-selective cation channels, most of which are permeable to Ca2+, which is a well-established second messenger that modulates several intracellular signaling pathways and is involved in physiological and pathological conditions in various cell types. TRPs depolarize excitable cells by increasing the influx of Ca2+, Na+, and other cations. Most TRP families are activated by temperature variations, membrane stretching, or chemical agents and, therefore, are defined as polymodal channels. All TPRs are expressed, at some level, in the central nervous system (CNS) and ocular-related structures, such as the retina and optic nerve (ON), except the TRPP in the ON. TRPC, TRPM, TRPV, and TRPML are found in the retinal pigmented cells, whereas only TRPA1 and TRPM are detected in the uvea. Accordingly, several studies have focused on the search to unravel the role of TRPs in physiological and pathological conditions related to the eyes. Thus, this review aims to shed light on endogenous and exogenous modulators, triggered cell signaling pathways, and localization and roles of each subfamily of TRP channels in physiological and pathological conditions in the retina, optic nerve, and retinal pigmented epithelium of vertebrates.